2022
DOI: 10.1093/ageing/afac120
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of rehabilitation interventions including outdoor mobility on older adults’ physical activity, endurance, outdoor mobility and falls-related self-efficacy: systematic review and meta-analysis

Abstract: Objective To determine the effectiveness of community-based rehabilitation interventions which incorporate outdoor mobility on physical activity, endurance, outdoor mobility and falls-related self-efficacy in older adults. Design MEDLINE, Embase, CINAHL, PEDro and OpenGrey were searched systematically from inception to June 2021 for randomised controlled trials (RCTs) of community-based rehabilitation incorporating outdoor mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Services that help people go outdoors seem invaluable for those with limited networks to reduce concerns about falling and activity restriction, particularly later post-discharge. However, rehabilitations incorporating outdoor mobility components did not show improvements in falls-related self-efficacy, possibly in part due to an absence of targeting environmental barriers related to mobility [ 69 ]. In support, an intervention providing walking maps for the local community environment improved time spent walking outdoors [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Services that help people go outdoors seem invaluable for those with limited networks to reduce concerns about falling and activity restriction, particularly later post-discharge. However, rehabilitations incorporating outdoor mobility components did not show improvements in falls-related self-efficacy, possibly in part due to an absence of targeting environmental barriers related to mobility [ 69 ]. In support, an intervention providing walking maps for the local community environment improved time spent walking outdoors [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 40 ). By persisting in vigorous-intensity exercise, not only can the risk of depression in older chronic comorbidities patients be reduced ( 41 ), but also their confidence in their own abilities ( 42 ) can be improved, believing that they can make positive changes in their physical health. These factors can enable respondents to more positively evaluate their health status.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that moderate exercise has a predictive effect on improving health and quality of life (38). Individuals who actively participate in sports activities are able to maintain or improve their physical abilities and better complete daily tasks in daily life (39), leading respondents to make better health selfrated health status. Meanwhile, vigorous-intensity exercise may have a positive effect on the endocrine system, such as promoting the release of neurotransmitters such as endorphins and dopamine, thereby improving emotional and psychological states (30).…”
Section: Discussionmentioning
confidence: 99%
“…These applications are useful for clinicians, patients, people interested in monitoring their lives state and health, and some that help implement telerehabilitation techniques. Finally, the review in [84] is focused on the proportion of older adults that can move outdoors and how rehabilitation could help to increase this activity through a review of 29 studies that talk about mobility programs for outdoor environments.…”
Section: Bci Applications For Rehabilitation 91 Rehabilitationmentioning
confidence: 99%